Exploration of the potential mechanism of Banxia Xiexin Decoction for the effects on TNBS-induced ulcerative colitis rats with the assistance of network pharmacology analysis. (15th September 2021) - Wang, Weiwei; Xu, Congcong; Li, Xinye; Wang, Zibing; Yang, Jinchuan; Shen, Ye; Shi, Mengge; Chen, Lixia; Zhang, Lili; Guo, Yilin; Wang, Bing; Zhang, Tong; et al.
Abstract: Ethnopharmacological relevance: Banxia Xiexin Decoction (BXD), an ancient TCM prescription originating from Treatise on Febrile Diseases ( Shang Han Lun ) of the Han Dynasty, has been widely used in modern clinical practice, especially for gastrointestinal diseases, including ulcerative colitis (UC). However, the modern decoction method of BXD differs from that of the original method. Thus, an exploration of the influence of the different decoction methods on the pharmacological effects is interesting and significant. Aim of the study: This study aimed to systematically compare the pharmacological effects of extracts of BXD on TNBS induce UC rats that were prepared by different methods, the ancient method and the modern method. The findings may provide important information for the further mechanical exploration of the classical prescription, contributing to the rational application and enhancing the understanding of BXD in modern applications or scientific research. Methods: Fifty-four SD rats were randomly divided into the following nine groups at n = 6/group: control group; model group; salicylazosulfapyridine group; BXD ancient extraction method's low-dose group (BXD-AED-L, 3.6 g BXD-AED/kg), medium-dose group (BXD-AED-M, 7.2 g BXD-AED/kg), and high-dose group (BXD-AED-H, 14.4 g BXD-AED/kg); and BXD modern extraction method's low-dose group (BXD-MED-L, 1 g BXD-MED/kg), medium-dose group (BXD-MED-M, 2 g BXD-MED/kg), and high-dose group (BXD-MED-H, 4 g BXD-MED/kg). All the groups, except the control group, were rectally injected with 70 mg/kg ethanol solution containing TNBS (2, 4, 6-trinitrobenzenesulfonic acid) to establish the UC models. The pharmacological evaluations including disease activity index, colon weight index, macroscopic and histological evaluation of colon damage, and inflammatory cytokine levels (IL-4, IL-10, IL-1β, TNF-α, and IL-6)were measured. In the network pharmacology analysis, the "herbs-components-targets-disease" network was constructed and visually analyzed with which the targets with a strong correlation with UC were screened out. Results: The results showed that both BXD-AED and BXD-MED might alleviate the severity of UC with different degrees according to the majority of indices that were evaluated. At similar doses, the BXD-AED groups performed better compared with the BXD-MED groups. With the assistance of the network pharmacology analysis, some key active components (quercetin, baicalein, wogonin, and baicalin) related to the anti-UC/inflammation were screened out. The contents of the components in BXD-AED were higher than those in BXD-MED. The joint results of the study indicated that BXD, an ancient TCM compound prescription, is an effective drug candidate for the modern treatment of UC. Graphical abstract: Image 1